2008
DOI: 10.1183/09031936.00092607
|View full text |Cite
|
Sign up to set email alerts
|

Can CAP guideline adherence improve patient outcome in internal medicine departments?

Abstract: The impact of compliance with Italian guidelines on the outcome of hospitalised community-acquired pneumonia (CAP) in internal medicine departments was evaluated.All Fine class IV or V CAP patients were included in this multicentre, interventional, before-andafter study, composed of three phases: 1) a retrospective phase (RP; 1,443 patients); 2) a guideline implementation phase; and 3) a prospective phase (PP; 1,404 patients).Antibiotic prescription according to the guidelines increased significantly in the PP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
51
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 19 publications
3
51
0
3
Order By: Relevance
“…In the current issue of the European Respiratory Journal, two additional contributions to this topic are published [15,16]. The study from Italy [15] used a multicentre pre-post intervention design, based on Italian guidelines.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the current issue of the European Respiratory Journal, two additional contributions to this topic are published [15,16]. The study from Italy [15] used a multicentre pre-post intervention design, based on Italian guidelines.…”
mentioning
confidence: 99%
“…The study from Italy [15] used a multicentre pre-post intervention design, based on Italian guidelines. It evaluated patients at increased risk of death according to Pneumonia Severity Index class IV and V but excluded ICU patients hospitalised in a nonspecialist internal medicine ward.…”
mentioning
confidence: 99%
“…A few trials have previously compared BL, BLM, and FQ regimens in patients with CAP (5,12,13). In this study, we aimed to compare the effectiveness of these most frequently used antibiotic regimens in the realworld setting.…”
Section: Introductionmentioning
confidence: 99%
“…(4) Although there is no consensus in the literature, various studies have shown that the systematic use of CAP guidelines results in an increase in the proportion of patients treated as outpatients (with no worsening of outcomes), as well as in a reduction in 30-day mortality, in-hospital mortality, length of hospital stay, time to clinical stability, and complications in those treated as inpatients. (5)(6)(7)(8)(9) The primary objective of the present study was to evaluate the agreement between the criteria used for hospitalization of CAP patients in the Hospital das Clínicas da Universidade Federal de Minas Gerais (HC/UFMG, Federal University of Minas Gerais Hospital das Clínicas), located in the city of Belo Horizonte, Brazil, in the 2005-2007 period and those of the Brazilian Thoracic Association guidelines, as well as to evaluate the association of that agreement with 30-day mortality. The secondary objective of the study was to evaluate the association between the agreement of the treatment given with that recommended in the Brazilian guidelines for CAP and length of hospital stay, microbiological profile, 12-month mortality, incidence of complications, need for ICU admission, need for mechanical ventilation, and variables associated with 30-day mortality.…”
Section: Introductionmentioning
confidence: 99%